Organizational Restructuring in Administrative Management: A Case Study in a Mining Company in Lucma, Gran Chimú - Peru (LACCEI, 2024)
The general objective of this investigation was to determine the influence of organizational restructuring on the administrative management of the Huayday de Lucma - Gran Chimú Mine in the year 2022. The type of research was applied, at an explanatory level, with an experimental design with a pre-grade experimental and qualitative, the instrument to collect the data was the questionnaire, applied to 25 clients of the company, which were registered in a database in Microsoft Excel. For subsequent validation, the polytomous Aiken V technique and Cronbach's alpha were used, which in turn made it possible to measure the degree of reliability. In the results, the percentages and averages that allowed to demonstrate the hypothesis were observed, they also consist of variations in reference to before and after the implementation where the four dimensions of administrative management: planning, organization, direction and control, represented the following changes , 4% of the clients surveyed affirmed that the management level was bad while 96% considered it regular, by establishing management strategies it allowed improving the level of clients who considered administrative management regular by 36% and 64 % of customers who found it excellent. Finally, this investigation, by admitting the alternative hypothesis and rejecting the null hypothesis, concluded that the application of the strategies did influence and allowed to improve the level of administrative management by reinforcing the four fundamental pillars for good management. Likewise, its implementation benefited the functionality of the administrative processes by optimizing its management activities and adhering to new guidelines imposed by the company that allows it to fulfill its tasks and requirements more efficiently.